Asymmetric price transmission effect of corn on hog: evidence from China - Gangyi WANG; Runxiang SI; CuiXia LI; GuiTong ZHANG; Nengyue ZHU (Agricultural Economics (AGRICECON), 2018)
In this study, we used monthly corn price and hog price data from January 2000 to June 2015 to conduct an empirical analysis based on a smooth transition regression (STR) model. The analysis confirms and explains the asymmetric transmission mechanism and process of the smooth transformation of corn prices to hog prices and measures the mechanism conversion threshold. Using the smooth transformation mechanism and its threshold as its foundations, this study breaks up continuous smooth transfer price volatility transmission effects into completely linear, not completely linear, and nonlinear mechanism states. Based on these states, the influence of corn price on hog price fluctuation is attributed to cost-push inflation, risk stabilisation effects, and the coexistence of cost-push and risk-stabilisation effects from the perspective of adaptive expectations.